2020
DOI: 10.1101/2020.06.28.176248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phosphorylation modulates liquid-liquid phase separation of the SARS-CoV-2 N protein

Abstract: The nucleocapsid (N) protein of coronaviruses serves two major functions: compaction of the RNA genome in the virion and regulation of viral gene transcription in the infected cell1–3. The N protein contains two globular RNA-binding domains surrounded by regions of intrinsic disorder4. Phosphorylation of the central disordered region is required for normal viral genome transcription5,6, which occurs in a cytoplasmic structure called the rep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 79 publications
(110 reference statements)
10
56
0
Order By: Relevance
“…In this study, we expressed the N protein using a mammalian expression system, which more closely resembles the N protein produced in infected human cells (9). Consistent with Carlson et al and Chen et al, we observed that the N protein requires unstructured RNA fragments to form liquid condensates in physiological salt (38,54), suggesting that the positively charged protein and polyanion RNA form complex coacervates. The N protein is also capable of forming a biomolecular condensate in the presence of 1-5 kb viral RNA; however, these structures appear closer to gel-like filaments (38) and not as temperature-sensitive, liquid-like droplets observed by Iserman et al using bacterially expressed N (28).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, we expressed the N protein using a mammalian expression system, which more closely resembles the N protein produced in infected human cells (9). Consistent with Carlson et al and Chen et al, we observed that the N protein requires unstructured RNA fragments to form liquid condensates in physiological salt (38,54), suggesting that the positively charged protein and polyanion RNA form complex coacervates. The N protein is also capable of forming a biomolecular condensate in the presence of 1-5 kb viral RNA; however, these structures appear closer to gel-like filaments (38) and not as temperature-sensitive, liquid-like droplets observed by Iserman et al using bacterially expressed N (28).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with Carlson et al and Chen et al, we observed that the N protein requires unstructured RNA fragments to form liquid condensates in physiological salt (38,54), suggesting that the positively charged protein and polyanion RNA form complex coacervates. The N protein is also capable of forming a biomolecular condensate in the presence of 1-5 kb viral RNA; however, these structures appear closer to gel-like filaments (38) and not as temperature-sensitive, liquid-like droplets observed by Iserman et al using bacterially expressed N (28). However, in agreement with Iserman et al, we found that the structure of the RNA itself affects N condensation; base-paired or G-quadruplex-containing RNA produce irregularly shaped, gel-like condensates, similar to viral RNA (28).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations